Removal of chromium (VI) from polluted waters using powders of leaves or their ashes of some herbal plants - Krishna Veni, V; Ravindhranath, K (Journal of Experimental Sciences, 2012)
An investigation is made to explore the surface sorption abilities of powders of leaves and their ashes of some herbal plants. Achyranthes aspera, Mentha, Emblica officinalis, Azadirachta indica,, Hybiscus roja sinensis and Ocimum sanctum have been found to have strong affinity towards Chromate at low pH values. Physicochemical parameters such as pH, time of equilibration and sorbent concentration have been optimized for the maximum % removal of Chromium (VI) from waste waters. The minimum dosage and equilibration time needed for the maximum removal of Chromate is found to be less for the ashes of leaves than with the raw leaves powders. More than 90% of extractability for Chromium (VI) has been achieved with some of these bio-sorbents. The presence of tenfold excesses of Cations : Ca2+, Mg2+, Cu2+, Zn2+ and Ni2 +, marginally effected the % removal of Chromium (VI) while anions: Sulphates, Nitrate, Cl- , Phosphate and F- showed some interference with some sorbents. The adoptability of the methodologies developed in this work are tested with respect to diverse waste water samples collected from industrial effluents and in natural lakes and found to be remarkably successful.